Appendix 4.6: Marcos Diary Entry, 15 September 1971 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Besides his meeting with Justice Fred Ruiz Castro, of interest here is Marcos’s implicit claim of a (tenuous) link of the Plaza Miranda bombing of 21 August 1971 to Sen. Benigno “Ninoy” Aquino Jr. Marcos’s legal craftiness is also on show here: he notes that detainees can be moved from an area where the suspension of the privelege of the writ of habeas corpus has been lifted to one where the suspension remains in effect, thus allowing longer detention without charge.